The current health of the signing Deaf community in the UK compared with the general population: a cross-sectional study. Issue 1 (25th January 2015) - Emond, Alan; Ridd, Matthew; Sutherland, Hilary; Allsop, Lorna; Alexander, Andrew; Kyle, Jim
Abstract : Objectives: To assess the current health of the Deaf community in the UK and compare with the general population. Design: A quota sample of adult Deaf British Sign Language (BSL) users underwent a health assessment and interview in 2012–2013. Comparative data were obtained from the Health Survey for England (HSE) 2011 and the Quality Outcomes Framework (QOF) 2012. Setting: Participants completed a structured interview and health assessment at seven Bupa centres across the UK, supported in BSL by Deaf advisers and interpreters. Participants: 298 Deaf people, 20–82 years old, 47% male, with 12% from ethnic minorities. Main outcome measures: Self–reported health conditions, medication usage, tobacco and alcohol consumption; measured blood pressure (BP), body mass index, fasting blood sugar and lipid profile. Results: Rates of obesity in the Deaf sample were high, especially in those over 65 years, and 48% were in a high risk group for serious illness. High BP readings were obtained in 37% of Deaf people (21% in HSE): 29% were unaware of this (6% in HSE). Only 42% of Deaf people being treated for hypertension had adequate control, compared with 62% of the general population. Deaf people with self-reported cardiovascular disease (CVD) were significantly less than the general population. One-third of Deaf participants had total cholesterol >5 mmol/L but although control rates were high compared with HSE, treatment rates for self-reported CVD were half the general population rate. Eleven per cent of Deaf participants had blood sugar at prediabetic or diabetic levels, and 77% of those at prediabetic levels were unaware of it. Deaf respondents self-reported more depression (31% of women, 14% of men), but less smoking (8%) and alcohol intake (2–8 units/week). Conclusions: Deaf people's health is poorer than that of the general population, with probable underdiagnosis and undertreatment of chronic conditions putting them at risk of preventable ill health.